Quantum dot solar cells - Wang, Zhiming M.; Wu, Jiang (Lecture Notes in Nanoscale Science and Technology, 2014)
The third generation of solar cells includes those based on semiconductor quantum dots. This sophisticated technology applies nanotechnology and quantum mechanics theory to enhance the performance of ordinary solar cells. Although a practical application of quantum dot solar cells has yet to be achieved, a large number of theoretical calculations and experimental studies have confirmed the potential for meeting the requirement for ultra-high conversion efficiency. In this book, high-profile scientists have contributed tutorial chapters that outline the methods used in and the results of various quantum dot solar cell designs, including quantum dot intermediate band solar cells, hot electron quantum dot solar cells, quantum-dot sensitized solar cells, colloidal quantum dot solar cells, hybrid polymer-quantum dot solar cells, and MEG quantum dot solar cells. Both theoretical and experimental approaches are described. Quantum Dot Solar Cells helps to connect the fundamental laws of physics and the chemistry of materials with advances in device design and performance. The book can be recommended for a broad audience of chemists, electrical engineers, and materials scientists, and is suitable for use in courses on materials and device design for advanced and future optoelectronics. Features comprehensive coverage of novel technologies for quantum dot solar cells Written by leading experts in the corresponding research areas Supplies the keys to understanding the latest technologies for third-generation solar cells Provides a foundation for future research in materials and optoelectronics for energy applications